Ruthenium polypyridine complexes with triphenylamine groups as antibacterial agents against Staphylococcus aureus with membrane-disruptive mechanism - Jiang, Li; Ma, Yuanyuan; Xiong, Yanshi; Tan, Yanhui; Duan, Xuemin; Liao, Xiangwen; Wang, Jintao (Frontiers in Chemistry, 2022)
Due to the emergence and wide spread of methicillin-resistant Staphylococcus aureus, the treatment of this kind of infection becomes more and more difficult. To solve the problem of drug resistance, it is urgent to develop new antibiotics to avoid the most serious situation of no drug available. Three new Ru complexes [Ru (dmob)2PMA] (PF6)2 (Ru-1) [Ru (bpy)2PMA] (PF6)2 (Ru-2) and [Ru (dmb)2PMA] (PF6)2 (Ru-3) (dmob = 4,4′-dimethoxy-2,2′-bipyridine, bpy = 2,2′-bipyridine, dmb = 4,4′-dimethyl-2,2′-bipyridine and PMA = N-(4-(1H-imidazo [4,5-f] [1,10] phenanthrolin-2-yl) -4-methyl-N-(p-tolyl) aniline) were synthesized and characterized by 1H NMR, 13C NMR and HRMS. The detailed molecular structure of Ru-3 was determined by single crystal X-ray diffraction. Their antibacterial activities against Staphylococcus aureus (Staphylococcus aureus) were obvious and Ru-3 showed the best antibacterial effect with the minimum inhibitory concentration value of 4 μg ml−1. Therefore, further study on its biological activity showed that Ru-3 can effectively inhibit the formation of biofilm and destroy cell membrane. In vitro hemolysis test showed that Ru-3 has almost negligible cytotoxicity to mammalian red blood cells. In the toxicity test of wax moth insect model, Ru-3 exhibited low toxicity in vivo. These results, combined with histopathological studies, strongly suggest that Ru-3 was almost non-toxic. In addition, the synergistic effect of Ru-3 with common antibiotics such as ampicillin, chloramphenicol, tetracycline, kanamycin and gentamicin on Staphylococcus aureus was detected by chessboard method. Finally, in vivo results revealed that Ru-3 could obviously promote the wound healing of Staphylococcus aureus infected mice.